Experiences and Perceptions of Ophthalmic Simulation-Based Surgical Education in Sub-Saharan Africa - Annoh, Roxanne; Morgon Banks, Lena; Gichuhi, Stephen; Buchan, John; Makupa, William; Otiti, Juliet; Mukome, Agrippa; Arunga, Simon; Burton, Matthew J.; Dean, William H. (Journal of surgical education, 2021)
Simulation-based surgical education (SBSE) can positively impact trainee surgical competence. However, a detailed qualitative study of the role of simulation in ophthalmic surgical education has not previously been conducted. OBJECTIVE: To explore the experiences of trainee ophthalmologists and ophthalmic surgeon educators’ use of simulation, and the perceived challenges in surgical training. METHODS: A multi-center, multi-country qualitative study was conducted between October 2017 and August 2020. Trainee ophthalmologists from six training centers in sub-Saharan Africa (SSA) (in Kenya, Uganda, Tanzania, Zimbabwe and South Africa) participated in semi-structured interviews, before and after an intense simulation training course in intraocular surgery. Semi-structured interviews were also conducted with experienced ophthalmic surgeon educators. Interviews were anonymized, recorded, transcribed and coded. An inductive, bottom-up, constant comparative method was used for thematic analysis. RESULTS: Twenty-seven trainee ophthalmologists and 12 ophthalmic surgeon educators were included in the study and interviewed. The benefits and challenges of conventional surgical teaching, attributes of surgical educators, value of simulation in training and barriers to implementing ophthalmic surgical simulation were identified as major themes. Almost all trainees and trainers reported patient safety, a calm environment, the possibility of repetitive practice, and facilitation of reflective learning as beneficial aspects of ophthalmic SBSE. Perceived barriers in surgical training included a lack of surgical cases, poor supervision and limited simulation facilities. CONCLUSIONS: Simulation is perceived as an important and valuable model for education amongst trainees and ophthalmic surgeon educators in SSA. Advocating for the expansion and integration of educationally robust simulation surgical skills centers may improve the delivery of ophthalmic surgical education throughout SSA.
Keywords: Ophthalmology; Training; Simulation; Education